2008
DOI: 10.1007/s11104-008-9729-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of nitrate concentration in seepage water under a mature Norway spruce [Picea abies (L.) Karst] stand before and after clear cut

Abstract: The spatial and temporal variability of the nitrate (NO 3 − ) concentration in seepage water below the main rooting zone of a mature spruce forest was investigated using 121 suction cups which were implemented in a 2×2 m grid at 40 cm depth in the mineral soil. Seepage was collected at least monthly during the vegetation period in 2005. In January 2006 a clear cut was performed on the plot and monthly seepage water was collected with 118 suction cups. Conventional and geostatistical methods were used to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…At HW, the forest floor was covered nearly exclusively by mosses (Table 4), and so herbs could not occupy the clear cut rapidly enough to reduce NO 3 -concentrations more effectively. Similar results were found at a further clear-cut experiment at Höglwald, which was performed in close vicinity some years later (Kohlpaintner et al 2009). However, even when measuring places were significantly covered with ground vegetation ([60% coverage) the average reduction in nitrate concentration was small.…”
Section: Spatial and Temporal Variability In Nitrate Leachingsupporting
confidence: 82%
See 3 more Smart Citations
“…At HW, the forest floor was covered nearly exclusively by mosses (Table 4), and so herbs could not occupy the clear cut rapidly enough to reduce NO 3 -concentrations more effectively. Similar results were found at a further clear-cut experiment at Höglwald, which was performed in close vicinity some years later (Kohlpaintner et al 2009). However, even when measuring places were significantly covered with ground vegetation ([60% coverage) the average reduction in nitrate concentration was small.…”
Section: Spatial and Temporal Variability In Nitrate Leachingsupporting
confidence: 82%
“…Average peak concentrations were up to 2018 lmol c L -1 (BH) and 2595 lmol c L -1 (HW), with up to 3675 lmol c L -1 at single suction cups (HW). Similar results were observed following a later clear cut at HW (see Kohlpaintner et al 2009); however, higher NO 3 -concentrations were found after liming of the spruce stand (see Huber et al 2006b), where large amounts Clear cut and replant 1989-1994 1995-1999 1996 1997 1998 1999 1995 Jan Höglwald Ballyhooly Fig. 9 Potassium (K ? )…”
Section: Nitrate Leachingsupporting
confidence: 69%
See 2 more Smart Citations
“…The validation of simulated NO 3 − concentrations at single sampling locations is generally difficult due to the high variability of NO 3 − concentrations in seepage water [104][105][106][107]. Therefore, the losses with seepage water [111].…”
Section: Trends In Nitrate Concentrationsmentioning
confidence: 99%